Visualizing Endogenous Necrosomes in Necrosomes by In Situ Proximity Ligation Assay. Issue 2 (23rd February 2022) - Liang, Wei; Yuan, Junying
Abstract: Necroptosis is a regulated form of necrosis that has been shown to participate in the pathogenesis of major human inflammatory and neurodegenerative diseases. Formation of a necrosome, composed of the RIPK1/RIPK3 complex, drives the execution of necroptosis. Although the co‐immunoprecipitation (co‐IP) assay has been widely used as a biochemical protocol for studying necrosomes, the technical limitations of co‐IP prevent its use for identifying necrosomes in complex tissues and for investigating the subcellular localization of necrosomes. The development of a specific assay for visualizing necrosomes in situ is needed. Here, we developed an in situ proximity ligation assay (PLA), which converts the detection of protein‐protein interaction to detection of DNA product by rolling‐circle amplification for investigating the endogenous necrosome in situ and in tissues. This protocol describes an in situ PLA that we have developed for visualizing endogenous necrosomes in necroptosis in both human and mouse cells and in mouse embryos with sensitivity and specificity. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Detection of RIPK1/RIPK3 interaction by in situ proximity ligation assay in human and mouse cells